2011
DOI: 10.4171/rmi/654
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic polynomials and tangent measures of harmonic measure

Abstract: We show that on an NTA domain if each tangent measure to harmonic measure at a point is a polynomial harmonic measure then the associated polynomials are homogeneous. Geometric information for solutions of a two-phase free boundary problem studied by Kenig and Toro is derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 16 publications
(41 reference statements)
1
34
0
Order By: Relevance
“…Finally we note that the arguments in [21] are further enhanced by Badger in [3]. In order to state these results let VMO (μ + ) denote the space of functions on ∂Ω + that are of vanishing mean oscillation with respect to μ + .…”
Section: Proof Of Theorem 4 and Closing Remarksmentioning
confidence: 89%
See 2 more Smart Citations
“…Finally we note that the arguments in [21] are further enhanced by Badger in [3]. In order to state these results let VMO (μ + ) denote the space of functions on ∂Ω + that are of vanishing mean oscillation with respect to μ + .…”
Section: Proof Of Theorem 4 and Closing Remarksmentioning
confidence: 89%
“…Section 5 and Section 6 are devoted to the proof of Theorem 3 and Theorem 4, respectively. In Section 6 we also make some closing remarks concerning work in [21] and [3].…”
Section: ) Is Reifenberg Flat With Vanishing Constant and N ∈ Vmo(δ(wmentioning
confidence: 99%
See 1 more Smart Citation
“…In [13], Kenig and Toro showed that solutions for a certain two-phase free boundary problem for harmonic measures on two-sided domains in R n are locally well approximated by H in a Hausdorff distance sense. Refined information about the structure and size of the free boundary was obtained by Badger [1,2] by studying the geometry of abstract sets approximated by H and measures on their support. For instance, in [2], Badger showed that, if A ⊆ R n is closed, A is locally well approximated by H, and A looks pointwise on small scales like the zero set of a homogeneous harmonic polynomial, then A = A 1 ∪ A 2 , where A 1 is locally well approximated by G(n, n − 1), while near each x ∈ A 2 the set A looks locally like the zero set of a homogeneous harmonic polynomial of degree at least 2.…”
Section: Metadefinitionmentioning
confidence: 99%
“…Lemma 3.6 ( [Ba2]). If µ is a measure on R n , x ∈ supp (µ), and ν ∈ Tan(µ, x) such that 0 ∈ supp (ν), then Tan(ν, 0) ⊆ Tan(µ, x).…”
Section: Geometry Of Kp Cone Approximated Setsmentioning
confidence: 99%